2004
DOI: 10.1111/j.1442-2042.2003.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative transesophageal echocardiography for inferior vena caval tumor thrombus in renal cell carcinoma

Abstract: Background : We investigated the advantages of intraoperative transesophageal echocardiography (TEE) during inferior vena caval tumor thrombectomy in renal cell carcinoma (RCC). Methods : Five patients with RCC that extended into the inferior vena cava (IVC) underwent radical nephrectomy. To remove the tumor thrombus in the IVC, an inflated Fogarty balloon catheter was used to pull the thrombus below the level of the hepatic veins with real-time TEE monitoring. Results : In all cases, TEE monitoring during sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…[14][15][16] Investigators have found TEE to be accurate in monitoring intraoperative embolic phenomena during tumor manipulation, 17 evaluating IVC tumor extension, 18 recognizing residual tumor after attempted resection, 19 and evaluating preload and cardiac function during IVC clamping. Oikawa and colleagues 20 described the additional use of intraoperative TEE to position an intracaval balloon above the tumor thrombus, thus enabling resection without the need to mobilize the liver.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Investigators have found TEE to be accurate in monitoring intraoperative embolic phenomena during tumor manipulation, 17 evaluating IVC tumor extension, 18 recognizing residual tumor after attempted resection, 19 and evaluating preload and cardiac function during IVC clamping. Oikawa and colleagues 20 described the additional use of intraoperative TEE to position an intracaval balloon above the tumor thrombus, thus enabling resection without the need to mobilize the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has also been used for dilation of ureteropelvic obstruction, 6 avulsion of posterior urethral valves, 7 retrieval of indwelling ureteral stents 8,9 or intraoperative thrombectomy of inferior vena caval tumor of renal cell carcinoma 10 in urological diseases. The Fogarty catheter can be easily passed from an incision of the pelvis into the upper ureter distal to the expected narrow site.…”
Section: Discussionmentioning
confidence: 99%
“…of tumor thrombi in the IVC or right atrium, intraoperative TEE can reveal tumor adherence to the IVC, mobility, and fragility-factors that greatly increase the risk of pulmonary embolism. 10 In our case, TEE enabled us to detect the cephalad extent of the thrombus and to quickly recognize the tumor's movement into the patient's tricuspid valve and embolization of the tumor thrombus into the main pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%